Pure shift FESTA An ultra-high resolution NMR tool for the analysis of complex fluorine-containing spin systems - Mycroft, Coral (Magnetic resonance in chemistry : MRC, 2023)
© 2023 The Authors. Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd.